Analisis Penanganan Kompensasi Delay pada Maskapai Lion Air terhadap Kepuasan Penumpang oleh PT Kokapura di Bandar Udara Jenderal Ahmad Yani Semarang - Habibah, Ina Wahyu Eva; Kusuma, Nur Makkie Perdana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Delay is a state of delayed flight at an airline. Delay compensation is the provision of compensation to passengers if there is a flight delay either in the form of goods or money in accordance with Ministerial Regulation Number 89 of 2015. The purpose of this research is to find out whether there is an effect between the provision of delay compensation on satisfaction passengers, and to find out whether passengers are satisfied with the provision of compensation according to PM Number 89 of 2015. The method used in this research is a quantitative method. The population in this study were passengers from Lion Air at Jenderal Ahmad Yani Airport, Semarang with a sample of 100 respondents. Data collection was carried out by observing and distributing questionnaires (questionnaires). In this study, data analysis used a one-sample test analysis calculation and a simple linear regression test. The results of this study state that the provision of delay compensation to passengers is in accordance with PM Number 89 of 2015. Based on the results of the t-test it can be stated that there is an effect of handling delay compensation on passenger satisfaction at Lion Air Airlines at Jenderal Ahmad Yani Airport, Semarang. While the one-sample test results that passengers are satisfied with the handling of the delay compensation provided in accordance with PM Number 89 of 2015. Keywords : delay compensation, passenger satisfaction, one sample test analysis and simple linear regression analysis.